A Quadruple Band-Notched SWB MIMO Antenna with Enhanced Isolation Using Wiggly Line - Chaudhary, A. K.; Manohar, M. (Společnost pro radioelektronické inženýrství, 2024)
A novel quadruple band-notched spatial diversity/MIMO antenna for super wideband (SWB) application is investigated. The proposed antenna comprises two identical tapered semicircular radiators with two microstrip feedlines and a common slotted ground plane (CSGP), contributing a wide impedance bandwidth from 1.88-30 GHz. Further, a wiggly-line-decoupling-structure (WLDS) is introduced among the radiating ports to maximize the average isolation, more than 24 dB. The first band-notched functionality at 2.4 GHz is produced by etching a meandering slot on the CSGP, while the remaining three notch bands at 3.5, 5.5, and 7.5 GHz are obtained by implanting open-ended-semicircular (OES), complementary-split-ring-resonator (CSRR), and elliptical-split-ring-resonator (ESRR) slots in each radiating patch. The designed and fabricated results for the two and four elements are analyzed, which exhibit wideband characteristics, stable radiation pattern, higher efficiency (above 85%), and reasonably high peak gain within the working frequency, excluding the quadruple notched bands. Moreover, other essential parameters such as ECC, DG, CCL, and TARC have also been analyzed, showing the antenna's usefulness for radar imaging, cognitive radio, military, and long-range RF applications.
Keywords: Diversity antenna; quadruple band-notch; SWB; tapered semicircular patch; WLDS